2009
DOI: 10.1002/adma.200802094
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Nature of Ultrafast Polarization Dynamics of Ferroelectric Memory in the Multiferroic BiFeO3

Abstract: The vast majority of data-storage devices are based on ferroelectric or magnetic materials. [1,2] The magnetic-memory effect is derived from the spin order, while the ferroelectric memories are based on the spontaneous polarization of electric dipoles. In the quest for superior efficiencies, the operating speed of the devices based on these memories has become a major focus of research. The time needed for the memory parameter to respond to ultrafast electric, magnetic, or optical stimuli is vital to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
106
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(108 citation statements)
references
References 34 publications
(54 reference statements)
1
106
0
1
Order By: Relevance
“…9 From the applied point of view in photonics, it has been proposed that terahertz radiation from BFO films can be used in ferroelectric domain imaging and optical readout of the state of ferroelectric memories. 10,11 In addition, due to high optical transparency and large third order optical nonlinearities, BFO films are promising for applications in ultrafast photonic devices. 12,13 No matter the structural dependent emission of THz radiation or the nonlinear photonic devices, a detailed understanding of the interaction of electron and lattice over a picosecond time scale is an indispensable issue, 14 which is decisive for determining the functional properties of materials.…”
mentioning
confidence: 99%
“…9 From the applied point of view in photonics, it has been proposed that terahertz radiation from BFO films can be used in ferroelectric domain imaging and optical readout of the state of ferroelectric memories. 10,11 In addition, due to high optical transparency and large third order optical nonlinearities, BFO films are promising for applications in ultrafast photonic devices. 12,13 No matter the structural dependent emission of THz radiation or the nonlinear photonic devices, a detailed understanding of the interaction of electron and lattice over a picosecond time scale is an indispensable issue, 14 which is decisive for determining the functional properties of materials.…”
mentioning
confidence: 99%
“…12, 13 Rana et al reported that the ultrafast depolarization of ferroelectric order causes the structural dependent terahertz radiation in BFO. 16 Talbayev et al used the terahertz spectroscopy to interpret the spectrum of long-wavelength magnetic resonance modes of BFO crystal. 17 Coupling of light with mechanical degrees of freedom in BFO was reported by Kundys et al, the light-induced wavelength dependent size change of BFO single crystal can be understood from photostriction effect, a superposition of photovoltaic effect and electrostrictive effect.…”
mentioning
confidence: 99%
“…In previous studies, we have revealed that the THz radiation from ferroelectric materials reflected the direction and amount of spontaneous polarization. 16 Photoexcited carriers accelerated by the electric field induced by spontaneous polarization generate THz radiation polarized in the same direction as the spontaneous polarization.…”
mentioning
confidence: 99%